Differentiation-inducing factor-3 inhibits intestinal tumor growth in vitro and in vivo - Naoya Kubokura; Fumi Takahashi-Yanaga; Masaki Arioka; Tatsuya Yoshihara; Kazunobu Igawa; Katsuhiko Tomooka; Sachio Morimoto; Yoshimichi Nakatsu; Teruhisa Tsuzuki; Yusaku Nakabeppu; Takayuki Matsumoto; Takanari Kitazono; et al. (Elsevier, 2015)
Differentiation-inducing factor-1 (DIF-1) produced by Dictyostelium discoideum strongly inhibits the proliferation of various types of cancer cells by suppression of the Wnt/β-catenin signal transduction pathway. In the present study, we examined the effect of differentiation-inducing factor-3 (DIF-3), a monochlorinated metabolite of DIF-1 that is also produced by D. discoideum, on human colon cancer cell lines HCT-116 and DLD-1. DIF-3 strongly inhibited cell proliferation by arresting the cell cycle at the G0/G1 phase. DIF-3 reduced the expression levels of cyclin D1 and c-Myc by facilitating their degradation via activation of GSK-3β in a time and dose-dependent manner. In addition, DIF-3 suppressed the expression of T-cell factor 7-like 2, a key transcription factor in the Wnt/β-catenin signaling pathway, thereby reducing the mRNA levels of cyclin D1 and c-Myc. Subsequently, we examined the in vivo effects of DIF-3 in Mutyh−/− mice with oxidative stress-induced intestinal cancers. Repeated oral administration of DIF-3 markedly reduced the number and size of cancers at a level comparable to that of DIF-1. These data suggest that DIF-3 inhibits intestinal cancer cell proliferation in vitro and in vivo, probably by mechanisms similar to those identified in DIF-1 actions, and that DIF-3 may be a potential novel anti-cancer agent.